The Role Of Digital Skills In Improving Teachers’ Competencies At SDN Belo In The Society 5.0 Era - Nia indrawati; Azra Fauzi; Yuyun Yuningsih RS (Jurnal Ilmiah Mandala Education (JIME), 2025)
The era of Society 5.0 requires teachers to possess digital skills not merely as a complement but as a fundamental prerequisite for creating innovative, effective, and student-centered learning. This study aims to analyze the role of digital skills in improving teachers’ competencies at SDN Belo and to identify the supporting and inhibiting factors they encounter. This research employed a descriptive qualitative approach with five purposively selected teachers as subjects. Data were collected through in-depth interviews, observations, and documentation, then analyzed using thematic analysis techniques. The findings reveal that teachers have begun to adopt digital skills, albeit in relatively simple forms such as using PowerPoint, YouTube, and communication applications. The utilization of technology has been proven to enhance teaching effectiveness, student engagement, and teachers’ confidence. Nevertheless, limited ICT facilities, insufficient practical training, and disparities in digital literacy remain the main obstacles. These findings emphasize the importance of providing practical training, strengthening digital literacy, and improving infrastructure support from the government and educational institutions. Therefore, digital skills play a strategic role in fostering the professionalism of SDN Belo teachers in the Society 5.0 era.